Estudo comparativo entre a angiografia por OCT e a angiografia aom fluoresceína sódica sa maculopatia isquêmica diabética - Garcia, José Mauricio Botto de Barros (2016)
The purpose of this study is to compare fluorescein angiography and optical coherence tomography (OCT) angiography images of foveal avascular zone (FAZ) in patients with diabetic retinopathy (DR) with and without diabetic macular ischemia. Regarding our methods, the Wilcoxon signedrank test was used to compare area measurements and P values of < 0.05 were considered statistically significant. Fluorescein angiography and OCT angiography images were independently graded by 2 observers that reached agreement regarding quantitative diabetic macular ischemia according established protocols. The ischemic area was divided into “moderate” and ‘‘large’’ macular ischemia (with diabetic macular ischemia) and ‘‘small’’ (without diabetic macular ischemia) groups. Quantitative analyses of the FAZ were performed using custom software (ImageJ64; National Institute of Health - NIH; http://rsbweb.nih.gov/ij/; public domain). Considering our results, thirty-four eyes from 34 diabetic patients were enrolled. Subjects with diabetic macular ischemia presented a mean area on fluorescein angiography and OCT angiography of 0.68 + 0.53 mm2 and 0.58 + 0.35 mm2, respectively (p = 0.1374). Patients without diabetic macular ischemia presented a mean area on fluorescein angiography and OCT angiography of 0.19 + 0.67 mm2 and 0.20 + 0.79 mm2, respectively (p = 0.9594). The ICC for the FAZ measurements between the 2 observers on fluorescein angiography and OCT angiography was 0.96 and 0.92, respectively. Thereby, OCT angiography may represent a novel technique for the diagnosis of diabetic macular ischemia and could become an alternative to FA for this purpose.